Author Correction: Single human B cell-derived monoclonal anti-Candida antibodies enhance phagocytosis and protect against disseminated candidiasis - F. M. Rudkin (Nature Portfolio, 2019)
The original version of this Article contained errors in the author affiliations. Please see the associated correction for the full list of errors. These errors have been corrected in both the PDF and HTML versions of the Article.